The serpents of paradise a reader - Abbey, Edward 1927-1989 (Holt, 1995)
To speak for the voiceless was his mission. He was a virtuoso of the well-phrased thought in which style and content, symbol and meaning - each imbued with humor - come together to defy the powerful, reminding us always that preservation of wild nature is a key to a free spirit. And along with Emerson and Thoreau, Abbey, the uncompromising stylist, knew that the corruption of language follows the corruption of man. "Language," Abbey wrote, "seeks to transcend itself, 'to grasp the thing that has no name.'
Keywords: Nature -- Effect of human beings on -- Literary collections; Wilderness areas -- Literary collections; Mensch; Wildnis; Natur; West (U.S.) -- Literary collections; USA -- Weststaaten; Aufsatzsammlung